2004
DOI: 10.5230/jkgca.2004.4.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Cancer Occurring in a Patient with Plummer-Vinson Syndrome: A case report

Abstract: Plummer-Vinson syndrome (sideropenic dysphagia) is characterized by dysphagia due to an upper esophageal or hypopharyngeal web in patients with chronic iron deficiency anemia. The main cause of dysphagia is the presence of the web in the cervical esophagus, and abnormal motility of the pharynx or esophagus is also found to play a significant role in this condition. This syndrome is thought to be precancerous because squamous cell carcinoma of hypopharynx, oral cavity or esophagus takes place in 10% of those pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…It is often located below the cricoid cartilage of the upper esophagus, protruding into the esophageal lumen and blocking part of the lumen. 1,6 The incidence is about 1% of the total population and is found in 5~15% of dysphagia patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is often located below the cricoid cartilage of the upper esophagus, protruding into the esophageal lumen and blocking part of the lumen. 1,6 The incidence is about 1% of the total population and is found in 5~15% of dysphagia patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent single-center study in India, cancer was found in the hypopharynx and central esophagus in six out of 132 patients (4.5%), with rare cases accompanying advanced gastric cancer. 4,6 In addition to preventing the recurrence of symptoms, continuous iron supplementation is required until the anemia is corrected in order to prevent the progression of the esophageal web to oral, pharyngeal, esophageal, and/or gastric cancer.…”
Section: 10mentioning
confidence: 99%
See 1 more Smart Citation